Copysites: tourist attractions in the age of their architectural reproducibility - Bernhard, Bauer; Duccio, Canestrini (Journal of tourism and cultural change, 2019)
In this article we focus on those tangible assets that have been copied and imitated for reasons that are linked to tourism. What we call copysites are the replicas of places, buildings and sites that attract visitors interested in cultural heritage (tangible and intangible) and leisure activities, such as, entertainment, shopping, gastronomy etc. We analyse characteristic cases and acknowledge that the creation of copysites has different backgrounds: commercial interests, artistic and aesthetic motives, entertainment reasons, the joy to reproduce forms of success, preservation of the original sites, among others. We focus on who is content with visiting copies of monuments, sculptures, cities or 'fakelore' performances. On the basis of our examples we explain how far the principle of visiting replicated sites can be a success formula and why it seems so important for many tourists to see, check-in and tick-off activities and destinations, even if they are 'almost authentic'.